KOMPARASI PENERAPAN KURIKULUM MERDEKA DAN K-13 DI MTSN BATU - Rohman, Ahmad Roisur (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2024)
The curriculum is a reference to determine where we will achieve educational goals. At the time ofthe outbreak of the Covid -19 pandemic virus, it has encouraged the whole world to start learningin their own way through technology using distance learning methods or PJJ in a network or onlinesystem. The government through the Ministry of Education and Culture of the Republic of Indonesiahas taken steps to create a curriculum that is considered suitable for implementation during thecurrent COVID-19 pandemic outbreak. Namely by implementing an independent curriculum, eventhough before the pandemic occurred K-13 was the curriculum that was used as the main curriculumin every education unit, but after the ministry of education initiated a driving school that wasspecifically fostered, an independent learning curriculum emerged. But in fact, until now there arestill many schools that have not been able to and do not understand how to implement independentlearning. Although basically the independent curriculum is not too much different from the previouscurriculum, namely still emphasizing the achievement of competency attitudes, knowledge, andskills for the implementation of learning. However, this should also be a special study by thegovernment as the policy makers in the implementation of education so that the independent learningcurriculum can be applied to perfect K-13 so that it does not just become a program that is imposedon educational units. In this study the authors will discuss patterns of differences in implementationindependent learning curriculum and K-13 so that later teachers will no longer have difficultydifferentiating the application of implementing the independent curriculum and K-13.